Hyperdifferentiated murine melanoma cells promote adaptive anti-tumor immunity but activate the immune checkpoint system - Yukie Ando; Yutaka Horiuchi; Sara Hatazawa; Momo Mataki; Akihiro Nakamura; Takashi Murakami (OncoImmunology)
Accumulating evidence suggests that phenotype switching of cancer cells is essential for therapeutic resistance. However, the immunological characteristics of drug-induced phenotype-switching melanoma cells (PSMCs) are unknown. We investigated PSMC elimination by host immunity using hyperdifferentiated melanoma model cells derived from murine B16F10 melanoma cells. Exposure of B16F10 cells to staurosporine induced a hyperdifferentiated phenotype associated with transient drug tolerance. Staurosporine-induced hyperdifferentiated B16F10 (sB16F10) cells expressed calreticulin on their surface and were phagocytosed efficiently. Furthermore, the inoculation of mice with sB16F10 cells induced immune responses against tumor-derived antigens. Despite the immunogenicity of sB16F10 cells, they activated the PD-1/PD-L1 immune checkpoint system and strongly resisted T cell-mediated tumor destruction. However, in vivo treatment with immune checkpoint inhibitors successfully eliminated the tumor. Thus, hyperdifferentiated melanoma cells have conflicting immunological properties – enhanced immunogenicity and immune evasion. Inhibiting the ability of PSMCs to evade T cell-mediated elimination might lead to complete melanoma eradication.